2018
DOI: 10.1002/ecs2.2485
|View full text |Cite
|
Sign up to set email alerts
|

The cascade impacts of climate change could threaten key ecological interactions

Abstract: Climate change is triggering ecological responses all over the world as a result of frequent, prolonged droughts. It could also affect ecological interactions, particularly pollination and seed dispersal, which play a key role in plant reproduction. We used a tripartite interaction with a mistletoe, its pollinator and its disperser animals to gain insight into this issue. We studied flower and fruit production, and visitation rates during average (2012) and dry (2015) austral summers. Drought in our study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 57 publications
(126 reference statements)
1
32
0
Order By: Relevance
“…For the mesic site, precipitation during the driest summers was between 54 and 63% below the historic records (Figure 1). For the rainy site, summer precipitation during 2015 at the closest long-term meteorological station was the lowest, being 12.4 standard deviations below the mean of the period 1950-2017 (Fontúrbel et al, 2018). Summer and fall of 2016 were classified as the most severe drought in western Patagonia between 40 and 47 • S, with precipitation deficits larger than 50% (Garreaud, 2018).…”
Section: Site and Climate Descriptionmentioning
confidence: 89%
See 1 more Smart Citation
“…For the mesic site, precipitation during the driest summers was between 54 and 63% below the historic records (Figure 1). For the rainy site, summer precipitation during 2015 at the closest long-term meteorological station was the lowest, being 12.4 standard deviations below the mean of the period 1950-2017 (Fontúrbel et al, 2018). Summer and fall of 2016 were classified as the most severe drought in western Patagonia between 40 and 47 • S, with precipitation deficits larger than 50% (Garreaud, 2018).…”
Section: Site and Climate Descriptionmentioning
confidence: 89%
“…Moreover, there has been a warming trend in recent decades, although not as strong as in other areas worldwide (Lara et al, 2020). The summers of 2014-2015 and 2015-2016 were the driest recorded since 1950 in some parts of southern Chile (∼39 • 30 -41 • Fontúrbel et al, 2018;Urrutia-Jalabert et al, 2018). These dry periods (drought from here onwards), actually coincided with the first massive mortality event affecting Nothofagus forests in the area (Lara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, flowering plants are by far the most abundant group in our dataset -15,162 species -and apart from the three aforementioned groups, it is the most vulnerable group in terms of complete loss of species geographic ranges. The fact that flowering plants are projected to suffer substantial negative impacts increases the concerns about the vulnerability of biodiversity in general, due to possible future alterations to ecological interactions and ecosystem functioning 8,39,40 . In turn, the two most vulnerable tetrapod groups are amphibians and reptiles 15,[41][42][43] , yet mammals and birds also appear to be highly vulnerable in some countries (figures 4).…”
Section: Resultsmentioning
confidence: 99%
“…Rising global temperatures are having negative impacts on biodiversity, increasing the risk of species extinctions across the world [4][5][6][7][8] . These negative impacts appear to be geographically widespread but are of serious concern for regions of high biodiversity fostering large numbers of restricted and endangered species 9 .…”
mentioning
confidence: 99%
“…For pollinator‐dependent crops, yield can also be jeopardized due to climatic variability impacting pollinator communities (Arnold et al, ; Glenny, Runyon, & Burkle, ; González‐Varo et al, ). Increasing climatic extremities (Cai et al, ; Thornton, Ericksen, Herrero, & Challinor, ; Vasseur et al, ) has been shown to impact the complex plant–pollinator relationship (Fontúrbel, Lara, Lobos, & Little, ; Potts et al, ) that can potentially lead to severe yield instabilities (Klein et al, ). During rapid climate change, the increase in such variability will lead to significant ecological and economic impact (Vanbergen & Insect Pollinators Initiative, ).…”
Section: Introductionmentioning
confidence: 99%